ADWE-04 Ribavirin for treatment of chronic hepatitis e in transplant recipients – experience from our centre. (8th June 2018) - Boyd, Alexander; Bufton, Sally; Mutimer, David Mutimer; Elsharkawy, Ahmed
Abstract : Introduction: Hepatitis E infection usually causes self-limiting hepatitis in immunocompetent patients. In patients who have received solid organ or bone marrow transplants and take immunosuppressive drugs, a chronic or persistent hepatitis can develop defined by viremia for greater than 3 months. Spontaneous clearance can occur with reduction of immunosuppressive load. Failing this, there is evidence these patients can be successfully treated with ribavirin. The goal is sustained viral response (SVR) with undetectable Hepatitis E RNA in blood and stool for 6 months after treatment. A recent analysis of 69 patients with solid organ transplants reported SVR of 78%. Some success has also been seen in bone marrow transplants. We aim to present our experience of treating persistent Hepatitis E infection with ribavirin. Methods: Retrospective analysis of clinical records and the pathology database. Results: Following a screening program at the Queen Elizabeth Hospital, Birmingham we have treated 11 transplant recipients with ribavirin over the last 18 months. Transplant types included 4 liver, 3 kidney, 1 heart and kidney combined and 3 bone marrow. The median age of the cohort was 44, patients were a median of 2 years out from transplant and taking a median of 2 immunosuppressants. ALT was raised in all patients, median value 155 (46 to 599). Ribavirin treatment was given for 12 weeks and continued if stool remained RNA positive at week 12; the median course was 14 weeks. Ribavirin was generally well tolerated although one patient had a treatment break at 2 weeks due to diarrhoea and vomiting; 2 needed EPO support. SVR was observed in 10/11 patients (91%) of whom 9/10 (90%) have continued to show SVR until the present time (mean 2.2 months). ALT responded in all patients, median value 20 (11 to 31). One patient did not achieve SVR and relapsed at 3 months; one patient who did achieve SVR relapsed at 10 months. 2 bone marrow recipients had received high dose steroids for graft versus host disease (GvHD) and liver biopsy was undertaken to distinguish Hepatitis E from GvHD: in both cases the biopsy showed a non-specific chronic hepatitis in keeping with Hepatitis E. Conclusions: Our Results show SVR of 91% with ribavirin in persistent Hepatitis E infection in a diverse cohort with different types of transplant including bone marrow. The fact that all patients had abnormal ALT means that persistent Hepatitis E must be considered as a cause of raised liver enzymes in transplant recipients. Of particular interest is the need to distinguish GvHD from persistent Hepatitis E in bone marrow recipients as the therapeutic approaches are fundamentally different and increasing doses of steroids, and rituximab in one case, led to worsening viral loads in our cohort. Ongoing follow-up will take place in our cohort and look for late relapse.